Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/7444430
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Attenuates Oxidative Damage by Activating the Sirt1/Nrf2/HO-1 Signaling Pathway to Protect the Kidney from Ischemia-Reperfusion Injury

Abstract: Oxidative stress is a key component of renal ischemia/reperfusion (I/R) injury. Fucoxanthin (Fx), a marine carotenoid with enhanced antioxidant capacity, acts as a ROS inhibitor in diseases such as ischemic stroke and acute lung injury. We hypothesized that fucoxanthin could attenuate renal I/R-induced oxidative damage. C57BL/6 mice ( n = 30 ) were randomly assigned to sham, IR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…FoxO1 plays a key role in the maintenance of redox homeostasis. Overexpression of FoxO1 can induce endogenous antioxidant enzymes expression and enhance hydrogen peroxide scavenging [ 10 ]. Additionally, SIRT1 can deacetylate ly310 residue of RelA/p65 to downregulate NF-кB activity and inhibit proinflammatory mediators release [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FoxO1 plays a key role in the maintenance of redox homeostasis. Overexpression of FoxO1 can induce endogenous antioxidant enzymes expression and enhance hydrogen peroxide scavenging [ 10 ]. Additionally, SIRT1 can deacetylate ly310 residue of RelA/p65 to downregulate NF-кB activity and inhibit proinflammatory mediators release [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1), a member of the sirtuins family, exhibits a critical role in many biological processes, including oxidative stress, inflammatory response, aging, and energy homeostasis [ 7 9 ]. Emerging evidence has demonstrated that SIRT1 could protect against oxidative insults and inflammation in different research areas, such as ischemia reperfusion-induced renal, liver, brain, and heart injury [ 10 13 ]. In addition, the neuroprotective function of SIRT1 has emerged as a critical mechanism in a variety of central nervous system (CNS) diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Reperfusion during myocardial ischemia in AMI patients aggravates myocardial ischemic injury [6]. Clinically, infarct size is a vital parameter for measuring MI/R lesion, and myocardial infarction size is closely related to prognosis of the disease [7]. Salvianic acid A, a bioactive compound in Salvia miltiorrhiza Bge, is a phenolic compound which has been reported to exert therapeutic effects on patients with cardiac hypertrophy and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Trop J Pharm Res, July 2022; 21 (7): 1457 [16]. It affects the barrier function of endothelial cells: the proliferation of fibroblasts also slows down the degradation the extracellular matrix.…”
Section: Research Has Shown That Tgf-β Is An Important Fibrosis-promo...mentioning
confidence: 99%
“…SIRT1 has been proven to play a critical role in modulating a wide range of physiological processes, including apoptosis, DNA repair, inflammatory response, metabolism, cancer, and stress [ 19 , 20 ]. Previous studies have demonstrated that SIRT1 can protect against oxidative stress and inflammation in various research areas, including ischemic reperfusion-induced renal, brain, and heart injuries [ 21 , 22 , 23 ]. In recent years, SIRT1 has been recognized as particularly important in the pathogenesis of stroke [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%